Determining the parameters for the sizing of sediment traps in the city of Johannesburg - Raliengoane, Mankoe Francis (University of the Witwatersrand, Johannesburg, 2024)
Urban land practices usually involve soil compaction and vegetation removal as cities expand and grow. This has led to increased flood peak flows and high stormwater runoff volumes associated with sediments, nutrients and other pollutants that load downstream water resources. To address these issues, there has been a growth of practices involving Sustainable Drainage Systems (SuDS) for managing stormwater runoff quantity and quality from urban areas. For example, this involves the application of attenuation ponds, and wetlands which temporarily store urban stormwater runoff, thereby reducing the sediment loads, pollutants, and release of peak flows to the downstream water resources at flow rates that mimic the pre-development flow patterns. This practice is gaining momentum in South African urban areas, which are supported by the policies and legislation set up by local authorities to address stormwater management. However, these stormwater application practices often do not perform according to their design capacities because they get filled with sediments and their effectiveness in attenuating peak flows is reduced. Therefore, it is important to reduce sediments coming into these structures by applying sediment traps and basins located at the head of such structures. The sediment trap’s main function is to slow down the stormwater runoff and help in the reduction of sediments before stormwater runoff is discharged out of the construction site and other disturbed areas. The City of Johannesburg Stormwater Management By-laws and Stormwater Design Manual have limited information for the management of sediment using sediment traps and basins and which parameters need to be considered when sizing sediment traps. Therefore, the main aim of the current research was to determine the parameters that should be considered when sizing sediment traps specifically for the city of Johannesburg. The following parameters: design rainfall, daily rainfall, catchment area, evaporation, land cover and land use, percentage of permeable and impermeable areas, topographical data, peak flow, runoff volume, catchment topography, soil types and infiltration characteristics, sediment particle size distribution, sediment settling velocity, sediment loading rate/yield were modelled through Personal Computer Stormwater Management Model (PCSWMM), ArcSWAT ArcGIS, and Excel Spreadsheet Models. Further, the sensitivity analysis was undertaken using different values of imperviousness and infiltration rates while observing peak flow and runoff volume changes in PCSWMM outputs. Modelling in PCSWMM showed that peak flows and runoff volumes increased due to an increase in the values of the imperviousness used. However, the range of infiltration rates for the soils in both sub- catchments S22 and S23 did not change the peak flows and runoff volumes. Though it was not the scope of the current study, it was observed that higher infiltration rates than the ones that were determined from the sub-catchments S22 and S23 indeed reduced peak flows and runoff volumes. On the other hand, particle settling velocity showed that gravel particles took a short time to settle and required a smaller sediment trap iii storage capacity. In comparison, silt particles took longer to settle and required a larger sediment trap storage capacity. Lastly, sediment yield from both sub-catchments S22 and S23 showed that sediment yield is driven by rainfall, whereby months with high rainfall had higher sediment yield than the months with low rainfall. It is therefore, concluded that the following parameters: design rainfall, daily rainfall, evaporation, land cover and land use, percentage of permeable and impermeable areas, topographical data, contributing catchment area, peak flow, runoff volume, catchment topography, soil types and infiltration characteristics, sediment particle size distribution, sediment settling velocity, sediment loading yield should be considered by the engineers, designers and planners when sizing sediment traps in the City of Johannesburg and possibly in other places as well.
A research report submitted in fulfillment of the requirements for the Master of Science in the field of Civil and Environmental Engineering, In the Faculty of Engineering and the Built Environment , School of Civil and Environmental Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Sediment Traps; Urbanisation; Stormwater; SDG-11: Sustainable cities and communities